Singapore Grouper Iridovirus (SGIV) Inhibited Autophagy for Efficient Viral Replication - Li, Chen; Wang, Liqun; Liu, Jiaxin; Yu, Yepin; Huang, Youhua; Huang, Xiaohong; Wei, Jingguang; Qin, Qiwei (Frontiers in Microbiology, 2020)
Autophagy is a conserved catabolic process that occurs at basal levels to maintain cellular homeostasis. Most virus infections can alter the autophagy level, which functions as either a pro-viral or antiviral pathway, depending on the virus and host cells. Singapore grouper iridovirus (SGIV) is a novel fish DNA virus that has caused great economic losses for the marine aquaculture industry. In this study, we found that SGIV inhibited the autophagy pathway in grouper spleen (GS) cells which was evidenced by the changes of LC3-II, Beclin1 and p-mTOR levels. Further study showed that SGIV uses at least two strategies to inhibit autophagy: 1) increasing the cytoplasmic p53 level; and 2) encoding viral proteins (VP48, VP122, VP132) that competitively bind autophagy related gene 5 to affect LC3 conversion. Moreover, activation of autophagy by rapamycin or overexpressing LC3 decreased SGIV replication. These results provide an antiviral strategy from the perspective of autophagy.